Victimization and HIV Risks Among Croatian Female Sex Workers : exploring the mediationrole of depressiveness and the moderation role of socialsupport - Štulhofer, Aleksandar; Sinković, Matija; Božić, Jasmina; Baćak, Valerio (2014)
To assess the association between victimization and HIV vulnerability among Croatian female sex workers (FSWs), a survey involving 157 FSWs recruited from two largest urban areas was conducted in 2014. A majority of participants reported direct and indirect victimization, which was found to be significantly associated with condom use at most recent noncommercial sexual intercourse and STI diagnosis in the past 12 months. The association between victimization and STI diagnosis was partially mediated by depressiveness and moderated by social support. The buffering role of social support points to the importance of including counseling services in HIV prevention programs in Croatia.